Atherosclerosis Yesterday, Today and Tomorrow - Gianturco, Luigi (IntechOpen, 2018)
Atherosclerosis is a subject of enormous contention for cardiologists and in general for all medical doctors. With this publication we have given you a concise "state-of-the-art" look at the world of atheroma. Many other elements could be included and so it is only a brief analysis of "today" (the preventive medicine era) and "tomorrow" (transforming the cure medicine era into the care medicine era) but also remembering "yesterday" (the ex-cathedra medicine era). Let's hope our arteries are free from atherosclerotic events: have a good read!